Investigation of the usage potential of the evacuated tube and the flat plate collectors to assist an absorption chiller - Düzcan, Ahmed; Kara, Yusuf Ali (Elsevier Ltd, 2021)
In this study, the usage potential of the evacuated tube collectors (ETCs) and the flat plate collectors (FPCs) for assisting an absorption chiller (AC) are comparatively investigated by using TRNSYS software. ETC and FPC are examined under different load conditions and scenarios to see if the collectors satisfy the required source temperature for an absorption chiller system (ACS) with LiBr – H2O pair. Daily and seasonal analyses are carried out. Daily analyses consist of three scenarios: both the auxiliary heater and the load are turned off in the first scenario while only the load is turned on in the second; both the auxiliary heater and the load are turned on in the third scenario that is also performed for summer season as a fourth scenario. The working fluid in all scenarios is a heat transfer fluid (HTF). In the third scenario at 250 kg/h load, the maximum collector outlet temperature is 113 °C and 99 °C, the daily solar fraction (SF) is 83% and 57%, the temperature to load is 106 °C and 86 °C for ETC and FPC, respectively. In the seasonal analysis, the seasonal SF is 81% and 20.19% at 250 kg/h load for ETC and FPC, respectively. Higher temperature and SF are obtained when HTF is used instead of water. It has been observed that the required source temperature for ACS can be provided with ETC.
Keywords: Evacuated Tube Collector; Flat Plate Collector; Heat Transfer Fluid; Solar Absorption Chiller; Solar Fraction; TRNSYS